Goosebumps: the abominable snowman of Pasadena - Stine, R. L.; Walker, David (Vision Australia Information Library Service Melbourne, 2006)
Jordan Blake and his sister, Nicole, are sick of the hot weather in Pasadena. Then they are whisked off to Alaska where their father has been asked to photograph a mysterious snow creature. To their horror, it turns out to be the abominable snowman!